Intermittent high-volume hemofiltration promotes remission in steroid-resistant idiopathic nephrotic syndrome. (3rd July 2015) - Xie, Hua; Fang, Ming; Lin, Hongli; Li, Ping; Chen, Jilin; Sun, Yanling; Kang, Zhe
Abstract: Inflammation is a key part in the etiology and progression of idiopathic nephrotic syndrome (INS), we hypothesize that removing pro-inflammatory cytokines with intermittent high-volume hemofiltration (IHVHF) could improve the outcome in INS patients. The purpose of the current study is to examine whether IHVHF promotes remission in steroid-resistant INS. Fifty-one steroid-resistant INS patients were followed up on an open-label basis with prospective evaluations. Thirty-five patients received mycophenolate mofetil (SRD group) and 16 patients received drugs and IHVHF due to volume overload despite of diuretics (SRDF group). The rate of complete remission (CR) was analyzed. We also recruited 30 healthy individuals and 36 steroid-sensitive (SS) INS patients as controls to investigate the correlation of interleukin (IL)-8, IL-10, IL-6 and IL-17 with INS activity. Compared with the patients in the SRD group, the 6-month CR rate was higher (44% vs. 9%, p  < 0.001) and time to first CR was significantly shorter (7.3 ± 3.6 vs. 11.1 ± 5.3 months, p =  0.02) in the SRDF group. Serum IL-8 was highest in the SRDF group and reduced by IHVHF clearance. Serum IL-8 was lower during remission than at onset or recurrence of INS, whereas no significant difference was seen in the other cytokines. Receiver operating characteristic curve analysis demonstrated that serum IL-8 predicted steroid sensitivity with moderate accuracy (area under the curve = 0.79, 95% CI: 0.69–0.87). IHVHF promotes remission in patients with steroid-resistant INS and it may be partly due to serum IL-8 clearance.